Development of lychee flavored nata de coco in syrup - Tan, Jennifer Tan
The selection of lychee flavor variant, flavor concentration, nata harvest age and aging period (for flavor to be absorbed by the nata) which was well suited for the development of lychee flavored nata de coco in syrup was studies. The concentrations used for each of the 3 lychee flavor variants obtained were 1%, 0.5% and 0.25%, concentration by weight. These were used in the production of lychee flavored nata de coco in syrup samples, and were then subjected to sensory evaluation by 24 panelists. Fifteen centimeter unstructured line scales were used to evaluate the sensory characteristics of the samples. Results from th statistical analysis of the scores showed that variant 2, (FHI# 97019-zr) at 0.25% concentration by weight, should be sed. For the determination of a suitable nata age and aging period for flavor to be absorbed by the nata, 4 days, 6 days and 8 days old nata were used in the production of samples. These were all incorporated with 0.25% of variant 2. Three samples per harvest age were produced and aged for 1 day, 3 days and 5 days, respectively. Subsequent to aging, samples were subjected to sensory evaluation by 24 panelists. Fifteen centimeter unstructured line scales were also used for the evaluation of the sensory attributes of the samples. Results indicated that, 6 days old nata for 4 days old nata, and 5 days aging period were well suited for the production of the said product. Verification studies confirmed that 6 days old nata or 4 days old nata may be used.